Mitral Annular Kinetics, Left Atrial, and Left Ventricular Diastolic Function Post Mitral Valve Repair in Degenerative Mitral Regurgitation - Schiros, Chun G.; Ahmed, Mustafa I.; McGiffin, David C.; Zhang, Xiaoxia; Lloyd, Steven G.; Aban, Inmaculada; Denney, Thomas S.; Dell’Italia, Louis J.; Gupta, Himanshu (Frontiers in Cardiovascular Medicine, 2015)
Objective: The relationship of mitral annular (MA) kinetics to left ventricular (LV) and left atrial (LA) function before and after mitral valve repair has not been well studied. Here we sought to provide comprehensive analysis that relates to MA motions, LA and LV diastolic function post mitral valve repair. Methods: Three-dimensional analyses of mitral annular motion, LA function and LV volumetric and diastolic strain rates were performed on 35 degenerative mitral regurgitation (MR) patients at baseline and 1-year post mitral valve repair, and 51 normal controls, utilizing cardiac magnetic resonance imaging with tissue tagging. Results: All had normal LV ejection fraction (EF) at baseline. LV and LA EFs decreased 1-year post-surgery vs. controls. LV early-diastolic myocardial strain rates decreased post-surgery along with decreases in normalized early-diastolic filling rate, E/A ratio and early-diastolic MA relaxation rates. Post-surgical LA late active kick remained higher in MR patients vs. control. LV and LA EFs were significantly associated with peak MA centroid to apex shortening. Furthermore, during LV systolic phase, peak LV ejection and LA filling rates were significantly correlated with peak MA centroid to apex shortening rate, respectively. While during LV diastolic phase, both peak early diastolic MA centroid to apex relaxation rate and LA ejection rate were positively significantly associated with LV peak early diastolic filling rate. Conclusions— MA motion is significantly associated with LA and LV function. Mitral annular motion, left atrial function and left ventricular diastolic strain rates are still impaired one year post mitral valve repair. Long term effects of these impairments should be prospectively evaluated.